Laryngeal involvement in relapsing polychondritis: clinical and CT findings in 173 patients - Zhengang Wang; Xiao Bai; Ruohan Yu (RMD Open)
Introduction/objectives Relapsing polychondritis (RP) is a rare autoimmune disorder primarily affecting cartilaginous structures. We aimed to characterise the clinical features and CT findings of laryngeal involvement in RP, hypothesising that specific CT patterns correlate with clinical manifestations.Methods We retrospectively analysed 173 patients with confirmed RP. Demographic and clinical data were collected, and laryngeal, tracheal, and bronchial CT findings were reviewed. Statistical analyses identified factors associated with laryngeal involvement and airway stenosis.Results Notably, 66% of asymptomatic patients displayed CT evidence of airway damage, with laryngeal involvement in 41.1% (44/107), tracheal involvement in 80.9% (140/173), and bronchial involvement in 36.4% (63/107). Cricoid erosion and broadening with mucosal hyperplasia were the predominant laryngeal findings. Significant associations with laryngeal involvement included younger age at disease onset (p<0.05), longer disease duration (p<0.01) and multiorgan manifestations (p<0.01).Conclusions Laryngeal involvement is common in RP patients with airway manifestations, second only to tracheal involvement. CT findings of cricoid erosion and broadening are characteristic. Vigilant clinical monitoring is recommended for RP patients with identified risk factors to facilitate early detection and management. Future research should focus on developing targeted interventions for this high-risk subgroup of RP patients.